PHYTOCHEMICAL SCREENING OF SECONDARY METABOLID ETHYL ACETATE EXTRACT DURIAN RIND (Durio zibethinus Murr) COLLECTED FROM CENTRAL BENGKULU REGENCY” - riana versita (ANJANI Journal (Medical Science & Healthcare Studies), 2023)
Introduction: Durian (Durio zibenthinus Murr) is one of the genetic resources (SDGs) of the local plant of Bengkulu Province which has quite high economic value. The durian plant is a tropical plant in Southeast Asia. Methods: This study used laboratory tests to determine the secondary metabolites present in the rind of Durian (Durio zibenthinus Murr) during the phytochemical screening process using ethyl acetate solvent. Result and Discussion: Alkaloid compounds are characterized by changes in color in the sample after being dripped with Dragendroff, Mayer and Wagner reagents. In addition, the ethyl acetate extract of Durian peel (Durio zibenthinus Murr) also contains triterpenoid compounds, flavonoids and tannins which can be used in herbal medicine. However, it does not contain steroid compounds, saponins because at the time of the study there was no color change such as the color of the greenish-blue ring for steroids but rather a bluish-green color which can be seen to contain steroid compounds. Conclusion: from this study, the components contained in Durian peel (Durio zibenthinus Murr) were extracted with ethyl acetate solvent, namely alkaloids, flavonoids, triterpenoids and tannins.